DRUG-INDUCED GINGIVAL OVERGROWTHS: AN INSIGHT INTO MOLECULAR MECHANISMS - Gabriel Rotundu; Diana Tatarciuc; Bogdan Amărioarei; Dana Budală; Ruxandra Stan; Oana Butnaru; Alexandra Mârțu; Liliana Păsărin; Ionut Luchian (Romanian Journal of Medical and Dental Education)
Drug-induced gingival overgrowths (DIGO) represent a significant side effect of various pharmacological treatments, particularly anticonvulsants, immunosuppressants, and calcium channel blockers. This condition, characterized by the excessive growth of gum tissue, can lead to discomfort, aesthetic concerns, and periodontal complications. Understanding the molecular mechanisms underlying DIGO is crucial for developing effective preventive and therapeutic strategies. This review aims to provide an in-depth analysis of the cellular and molecular pathways implicated in DIGO, including the roles of fibroblasts, inflammatory mediators, and genetic predispositions. By elucidating the interactions between these factors, we seek to highlight potential targets for intervention. Additionally, the review discusses current research advancements and potential future directions in the study of DIGO. Through this comprehensive examination, we aim to enhance the understanding of the implications of these mechanisms.